Kinetics of biomass and sewage sludge pyrolysis: Thermogravimetric and sealed reactor studies - Ahuja P.; Singh P.C.; Upadhyay S.N.; Kumar S. (My University, 2025)
Biomass and sewage sludge decomposition is studied by a competitive model consisting of weight loss and char formation reactions. Non-linear optimization technique is used to simulate the experimental curves obtained by TGA by minimizing the sum of the squares functions. Pre-exponential factors and activation energy are obtained for both the reactions for heating rates of 10, 20 and 40 K/min for acacia wood, bagasse, rice husk, and sewage sludge respectively. The order of the reactions determined for sewage sludge are much higher than that of other biomass materials, whereas the activation energies are lower. Isothermal experimental studies resulted in much higher yields of char for all the four samples, and experiments carried out at various initial nitrogen gas pressures confirm that vapour-solid interactions are the cause of secondary char formation. Rice husk and sewage sludge yield higher amounts of secondary char due to the catalytic effect of the inorganics present in higher amounts in these samples.